Challenges and Considerations in Assessing GERD: A Critical Review of a Study in Southern Punjab, Pakistan [Letter] - Qureshi MI; Qadri M; Arshad A (Dove Medical Press, 2024)
Muneeba Iqbal Qureshi, Manahil Qadri, Abdullah Arshad Shaheed Mohtarma Benazir Bhutto Medical College, Karachi, PakistanCorrespondence: Muneeba Iqbal QureshiShaheed Mohtarma Benazir Bhutto Medical College, Lyari, Karachi, Pakistan, Email muneebaiqbal1@gmail.com